Analysis of activities in social media polish men's volleyball clubs of PlusLiga - Roksana Płonka (Nicolaus Copernicus University in Toruń, 2018)
The article has been written in order to present activities in social media of PlusLiga teams in Polish men's volleyball sport clubs. The aim of this report is to show the diversified social media management (Facebook and Instagram in particular) influence on the recipients statistics. The main research method for the given article is data obtained from club profiles on Instagram and Facebook. The Instagram data has underwent a detailed analysis as this social medium is one of the main tools of sports marketing, building and promoting a good image of sports teams. Thanks to the information provided, it is possible to determine at what stage is the social media sports marketing of the PlusLiga clubs. Eight teams with different positions in the league table from season 2017/18 were selected for the study. The presented results and charts are an original work and can be used to analyze the development of social media activities of men's volleyball teams.